2007
DOI: 10.1159/000113051
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Predictors for Residual Tumor after Surgery in Patients with Ovarian Carcinoma

Abstract: Objectives: Suboptimal debulking (>1 cm residual tumor) results in poor survival rates for patients with an advanced stage of ovarian cancer. The purpose of this study was to develop a prediction model, based on simple preoperative parameters, for patients with an advanced stage of ovarian cancer who are at risk of suboptimal cytoreduction despite maximal surgical effort. Methods: Retrospective analysis of 187 consecutive patients with a suspected clinical diagnosis of advanced-stage ovarian cancer undergoing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 77 publications
0
17
0
Order By: Relevance
“…Prior studies have correlated pre-operative ascites with surgical and perioperative clinical outcomes [10, 16, 17] including the ability to achieve optimal or complete (R0) cytoreduction. The present study confirms the findings of these smaller cohorts that identified ascites as a risk factor for sub-optimal cytoreduction [10], a factor well known to predict worse clinical outcomes [18].…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have correlated pre-operative ascites with surgical and perioperative clinical outcomes [10, 16, 17] including the ability to achieve optimal or complete (R0) cytoreduction. The present study confirms the findings of these smaller cohorts that identified ascites as a risk factor for sub-optimal cytoreduction [10], a factor well known to predict worse clinical outcomes [18].…”
Section: Discussionmentioning
confidence: 99%
“…We recognize that serum albumin levels would have been an interesting variable to consider, particularly given that this protein has been studied extensively as an indirect measure of nutrition and appears to be associated with inferior outcomes in ovarian cancer surgery. 27 Moreover, since cervical cancer patients undergo adjuvant chemotherapy and would be more vulnerable to a ventral hernia, the study would have benefited from the inclusion of these patients. We suspect an absence of these patients or any additional inadvertently excluded subjects was attributed to either a coding issue limiting the chart selection process, or because of general surgery referrals.…”
Section: Discussionmentioning
confidence: 99%
“…Low serum albumin and hemoglobin levels have been reported to predict residual tumor after debulking surgery for ovarian cancer [106].…”
Section: Prognostic Value Of the Preoperative Systemic Inflammatory Rmentioning
confidence: 99%
“…A recent study by Yoshida and colleagues in 2008 [106] observed that an elevated pretreatment C-reactive protein level (>5 mg/l) was associated with a poorer cancer-specific survival following treatment of muscle-invasive bladder cancer with chemo-radiotherapy.…”
Section: Prognostic Value Of the Preoperative Systemic Inflammatory Rmentioning
confidence: 99%